Home free - Lasky, Kathryn ([Pheonix, AZ] : Four Winds Press ; New York : Macmillan, 1985)
Fifteen-year-old Sam's fight to save a wilderness area for endangered eagles helps an autistic girl return to reality and reveals her strange hidden power.
Keywords: Autism -- Fiction; Eagles -- Fiction; Conservation of natural resources -- Fiction; Science fiction